ANALISIS HERMENEUTIKA PADA LIRIK LAGU TONDI-TONDIKU KARYA HERBERT ARUAN - Tampubolon, Elisabeth Rusmaniar; Heryana, Nanang; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Language functions as a means of communication between individuals and has a close relationship with literary works, because it contains a means for interaction between writers and readers. Language in literary works has special characteristics, one of which is interpretation. The aim of this research is to reveal the hidden meanings and messages in the lyrics of the song Tondi-tondiku by Herbert Aruan, a Batak musician, and its implications for learning Indonesian in high school. Using descriptive methods and Schleirmacher's Hermeneutics theory, this analysis shows that the grammatical and psychological meaning of song lyrics is revealed based on Schleirmacher's interpretation. Grammatical meaning includes the classification of various grammatical categories, such as pronouns, conjunctions, nouns, and others, as well as denotative and connotative meanings. While psychological meaning includes complex emotions such as love, loss, hope, and concern. This study also formulates recommendations for integrating this song into the Indonesian language curriculum in high school, especially class 14 of 2019.